2019
DOI: 10.1177/1048371319892241
|View full text |Cite
|
Sign up to set email alerts
|

Going Beyond “It Sounds Good”: Developing Student Capacity to Give Meaningful Feedback

Abstract: National Core Arts Standards require students to use feedback from peers to refine both their performances and their compositions in the artistic processes of Create and Perform. When asked to give feedback to a peer, many students stop at comments like “It sounds good,” and do not naturally give specific, meaningful feedback. Therefore, teachers need to develop the capacity of students to give meaningful feedback to each other. This article outlines strategies and activities for building a classroom rich in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In this standard, students as early as kindergarten are asked to apply personal and peer feedback to refine performances. Therefore, we also need to be teaching students how to give meaningful feedback (Hatch, 2020). When they do, many studies have shown that when students try to give feedback to their own performance, they are not as accurate as when they stop performing to listen to a peer instead (Hewitt, 2011).…”
Section: Anchor Standard 5: Rehearse Evaluate Refinementioning
confidence: 99%
“…In this standard, students as early as kindergarten are asked to apply personal and peer feedback to refine performances. Therefore, we also need to be teaching students how to give meaningful feedback (Hatch, 2020). When they do, many studies have shown that when students try to give feedback to their own performance, they are not as accurate as when they stop performing to listen to a peer instead (Hewitt, 2011).…”
Section: Anchor Standard 5: Rehearse Evaluate Refinementioning
confidence: 99%
“…Or, instead of performing, a few students might be designated as "listeners" and are focused on gathering observations about the ensemble during the performance trial. Students will need teachers to model how to give specific feedback and will need practice at this skill independently from effecting rehearsal strategies (Hatch, 2019).…”
Section: Observementioning
confidence: 99%